EVACUATION OF THE POPULATION IN THE EVENT OF FLOODING AND THREAT - М.Б. Арипходжаева; Хакимов Озодбек Хамиджонович (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: Humanity, entering the XXI century, can consider and analyze the impact of various disasters and other problems of the past centuries, the article presents various ways to eliminate all types of emergencies and evacuate the population. Evacuation is considered completed when all the population to be evacuated will be removed from the boundaries of the zone of action of the damaging factors of the source of emergency situations to safe areas. When forming this work, the requirements of the governing and regulatory documents in force during the evacuation of the population were taken into account.